Causal Ambiguity and Management Perception - Powell, T; Lovallo, D; Caringal, C (2006)
We integrate and extend research on causal ambiguity, indicating the principal causal paths from ambiguity to performance and discussing the connections between empirical findings and resource-based expectations. We then develop the linkage between causal ambiguity and management perception. Drawing on experimental and field research, we give testable propositions linking ambiguity, perception, and firm performance; integrate this research with studies of causal ambiguity; and suggest directions for future causal ambiguity research.